Self-Assembling Tacrolimus Nanomicelles for Retinal Drug Delivery - Vrinda Gote; Abhirup Mandal; Meshal Alshamrani; Dhananjay Pal (MDPI AG, 2020)
Neovascular age-related macular degeneration (AMD) is characterized by an increase in reactive oxygen species (ROS) and pro-inflammatory cytokines in the retinal pigment epithelium cells. The primary purpose of this study was the development of a clear, tacrolimus nanomicellar formulation (TAC-NMF) for AMD. The optimized formulation had a mean diameter of 15.41 nm, a zeta potential of 0.5 mV, and an entrapment efficiency of 97.13%. In-vitro cytotoxicity studies revealed the dose-dependent cytotoxicity of TAC-NMF on various ocular cell lines, such as human retinal pigment epithelium (D407), monkey retinal choroidal endothelial (RF/6A) cells, and human corneal epithelium (CCL 20.2) cells. Cellular uptake and in-vitro distribution studies using flow cytometry and confocal microscopy, respectively, indicated an elevated uptake of TAC-NMF in a time-dependent manner. Biocompatibility assay using macrophage RAW 264.7 cell line resulted in low production of inflammatory cytokines such as IL-6, IL-1β and TNF-α after treatment with TAC-NMF. There was a decrease in ROS in D407 cells pre-treated with sodium iodate (ROS inducing agent) after treating with TAC-NMF and tacrolimus drug. Similarly, there was a reduction in the pro-inflammatory cytokines and VEGF-A in D407 cells pretreated with sodium iodate. This indicates that TAC-NMF could lower pro-inflammatory cytokines and ROS commonly seen in AMD.